Intoxicação espontânea pelo Herbicida Clomazone em ovinos e reprodução experimental da enfermidade - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The toxic neuropathies in farm animals caused by pesticides represent an important group of degenerative diseases of the central and peripheral nervous system. However, little is known about the real impact of many of these toxic products on animals and humans and to the environment. The clomazone is a herbicide that has been widely used in southern Brazil and includes one of the most potent herbicides and supposedly safe, with low toxicity to animals and humans. To date, there are no reports of this herbicide poisoning in domestic animals. This study describes the spontaneous and experimental poisoning due to clomazone herbicide in sheep. In a flock of 103 sheep, approximately 20 showed clinical signs especially neurological and respiratory. The poisoning was experimentally reproduced in three sheep with the administration of 134mg/kg body weight of clomazone. Both in natural and experimental cases the clinical signs included tachypnea, anorexia, apathy and limited mobility with weakness in forelimbs and hind limbs, drag tweezers, and gait changes. Macroscopically, there were no significant changes. Microscopically, were observed especially vacuolization in the white matter of brain, perineuronal vacuoles and, hyperemia congestion of the leptomeningeal and neuropil vessels. Ultrastructurally, the vacuolar lesions in the brain correspond to dendritic and astrocytic processes swelling. From the data obtained it was concluded that the clomazone is a toxic agent capable of causing toxic neuropathy in sheep.
Spontaneous poisoning by Clomazone Herbicide in sheep and experimental reproduction of disease
Keywords: Doenças de ovinos; Clomazone; Neuropatia tóxica; Neuropatologia; Diseases of sheep; Clomazone; Toxic neuropathy; Neuropathology; CNPQ::CIENCIAS AGRARIAS